1998
DOI: 10.1097/00007890-199805150-00014
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Autoimmune Destruction of Syngeneic Islet Grafts in Spontaneously Diabetic Nonobese Diabetic Mice by a Combination of Avitamin D3 Analog and Cyclosporine1

Abstract: KH1060, an analog of 1,25(OH)2D3, delays autoimmune disease recurrence after syngeneic islet transplantation in NOD mice, both alone and especially in combination with CsA, possibly restoring tolerance to beta cells in 30% of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
77
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 26 publications
2
77
2
Order By: Relevance
“…Diabetic NOD mice transplanted with syngeneic islets show early recurrence of the disease [38,39]. Histological analysis indicates severe infiltration and destruction of more than 50% of the grafts already 6 days after transplantation [38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Diabetic NOD mice transplanted with syngeneic islets show early recurrence of the disease [38,39]. Histological analysis indicates severe infiltration and destruction of more than 50% of the grafts already 6 days after transplantation [38].…”
Section: Discussionmentioning
confidence: 99%
“…Histological analysis indicates severe infiltration and destruction of more than 50% of the grafts already 6 days after transplantation [38]. Both CD4+ and CD8+ T-cells producing Th1-type cytokines (principally IFN-γ), are involved in the destruction of beta cells [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has previously demonstrated that both insulitis and diabetes can be prevented or arrested in NOD mice by administration of 1␣,25(OH) 2 D 3 (26) or its nonhypercalcemic analogs (29). Moreover, recurrence of disease after syngeneic islet transplantation can be prevented by administration of these nonhypercalcemic analogs in combination with low doses of cyclosporin A (30). These studies also demonstrate that 1␣,25(OH) 2 D 3 induces an immune shift locally in the pancreas as well as in transplanted islet grafts that is characterized by downregulation of the Th1 cytokines and upregulation of Th2 cytokines.…”
mentioning
confidence: 99%